2011
DOI: 10.1002/jmri.22693
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic possibility of diffusion tensor imaging for the evaluation of myometrial invasion in endometrial cancer: An ex vivo study

Abstract: Our ex vivo study suggests that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer ex vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Current published studies include ex vivo and in vivo studies. [11][12][13][14][15][16] In 2006, threedimensional fibre architecture of the normal human uterus based on DTI has been ex vivo evaluated in five samples by Weiss et al 11 Toba et al 12 ex vivo study showed that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer. However, fractional anisotropy (FA) value of a normal uterus has not been thoroughly investigated yet.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
“…Current published studies include ex vivo and in vivo studies. [11][12][13][14][15][16] In 2006, threedimensional fibre architecture of the normal human uterus based on DTI has been ex vivo evaluated in five samples by Weiss et al 11 Toba et al 12 ex vivo study showed that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer. However, fractional anisotropy (FA) value of a normal uterus has not been thoroughly investigated yet.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
“…The study was carried out on a 3T MRI, and DTI was obtained with a b value of (0.600 smm -2 ) (10). In an ex vivo study published by Toba et al (8), data were obtained from five ex vivo organs of patients subjected to hysterectomy for medical reasons. In this study, a 4. were statistically higher than the tumor (0.216±0.05) (p<0.01…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion is not a one-dimensional process, and in the organized viscera, diffusion does not occur equally in all directions. The directionality of water diffusion is defined by anisotropy index (fractional anisotropy), which determines microstructural arrangement, like the quantity and direction of fibrous tissue (8,9). In tissues like the kidneys, due to the presence of collecting ducts and tubules, or the uterus, due to the muscle structures, diffusion has anisotropic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of DWI, and DTI sequences which serve as functional imaging in the MRI protocol for the evaluation of uterine pathologies have been offered by several papers [2,3,7,8] . Besides quantitative evaluation with values has been found out to be effective in the discrimination of malignancy from benign lesions [1720] .…”
Section: Dwi and Dti Of Diseased Uterusmentioning
confidence: 99%